Perancangan Karya Fotografi Sebagai Representasi Kompetensi Dalam Sertifikasi Fotografi - Nicholas Andersen Laurentius; Julius Andi Nugroho (Jurnal Riset Multidisiplin Edukasi, 2026)
Increasingly competitive job market conditions have intensified the demand for formal recognition of individual competencies through professional certification mechanisms. This study aims to design photographic works as a representation of competency in the photography certification process at LSP UNTAR. The method applied is Design Thinking, comprising five stages: empathize, define, ideate, prototype, and test, supported by data collection through observation, interviews, and literature review. The study produced seven photographic works representing technical, aesthetic, and conceptual competency mastery in accordance with LSP UNTAR's assessment indicators. The works encompass themes of urban life, public space, and social expression, each designed methodically based on certification standards. The findings confirm that a photography portfolio structured around competency indicators can effectively serve as valid evidence in a professional photography certification assessment.